BIM for public authorities: Basic research for the standardized implementation of BIM in the building permit process. (August 2019) - Plazza, D; Röck, M; Malacarne, G; Passer, A; Marcher, C; Matt, D T
Abstract: The building permit is an indispensable connection between the approval authority and the executive client within the construction process. Moreover, sustainability criteria do not have sufficient regard in the building permit process in the area of research. To lay the foundation for a state-of-the-art digitalization of the building permit process, the study identifies the information requirements relevant to implement the BIM methodology taking into consideration the available sustainability aspects relevant to the process. A detailed evaluation of the building permit process and the analysis of projects that have gained building permission in the last five years in the area of study of South Tyrol (Italy) gives us a better understanding of the organizational structure and responsibilities in the process. The authors use the data of in-depth process analysis to assess a defined catalogue of basic requirements for BIM methodology in the building permit process. As a result, the analysed BIM-integrated approach enables an early-stage identification of approval compliance, which can be evaluated in the building permit process. A good understanding of the current process must be considered a key factor of a successful introduction of BIM for the building permit procedure.